EFFECTS OF OCCLUSAL LOADS IN THE GENESIS OF NON-CARIOUS CERVICAL LESIONS - A FINITE ELEMENT STUDY - Andreea Stănuşi; Veronica Mercuţ; Monica Scrieciu; Mihaela Sanda Popescu; Monica Mihaela Crăiţoiu Iacob; Luminiţa Dăguci; Ştefan Castravete; Daniela Doina Vintilă; Mihaela Vătu (Romanian Society of Oral Rehabilitation, 2019)
Aim of the study This study investigated the magnitude and distribution of stress in a maxillary first premolar subjected to normal and heavy occlusal loads, that were directed vertically and horizontally, using Finite Element Analysis. Material and methods A virtual 3D model of a maxillary first premolar was created using the CT images of a 14 year-old patient and the physical and mechanical properties of the dental tissues used in other studies. We obtained 8 scenarios for the vertical loading and 8 scenarios for the horizontal loading. Results The magnitude and distribution of stress were the least favorable in the case of the heavy horizontal loading applied on the intact tooth. Conclusions Our study showed that the intact tooth was the most affected by stress regardless of the loading applied.